Lastnice gozda kot prezrt zgled - Bogataj, Nevenka (Kakovostna starost, 2010)
There is particular lack of knowledge of educationally passive old people in generally diverse group of old people. We were looking at this segment during our study circle monitoring by focusing to the female forest owners, who usually have lower formal education than men of the same age. It was not easy to get in touch with them as the most live in distant rural areas, their social inclusion is weak while public care for this segment of society lacks e.g. educational infrastructure for adult learning is not developed. The first quantitative and qualitative data of those, who we were able to address with this pilot research, show certain common characteristics along classic criteria e.g. their role in society. Their status does not offer any public reputation. Despite they let us use their property as access to forests in Slovenia is free their contribution to the development and life quality is not valued. However, we present an impression about their characteristics and their own judgement of their situation. We tried to interpret position of this social group from the point of view of their strength. Female forest owners are according our opinion a huge, but overlooked source of knowledge and values. Despite clear principles of economic development they resist in self limitation to support common and long-term benefits of society. Findings about old rural women are important for the future as they root in local environment and may serve as an example of broadly useful living style e.g. for the economic crisis period. Presentation of female forest owners, despite they base in a non-representative sample, gives us an insight into the Slovenian rural practice of old people what contributes to their more complex cognition and understanding.
Keywords: podeželsko prebivalstvo; rural population; Slovenia; Slovenija; woman; ženska; starejša oseba; elderly person; forest proprietress; lastnica gozda; gozdna posestnica; forest holder; lastnice; ženske; gozdovi; starejši ljudje